Comparison of clinical prognosis between prenatal and postnatal diagnosis of fetuses with complex congenital heart disease - Shuyan Wu; Le Chen; Jianhui He; Fengzhen Han; Yanping Jiang (Clinical and Experimental Obstetrics & Gynecology)
Background: The purpose of this study was to explore the clinical value and prognosis of the “prenatal diagnosis-postnatal treatment” model for fetuses with complex congenital heart disease (CHD) by directly comparing the outcomes between prenatal and postnatal diagnosis. Methods: A total of 126 infants with complex CHD diagnosed by prenatal diagnosis and 160 infants with complex CHD diagnosed by postnatal diagnosis in Guangdong Provincial People’s Hospital from January 2012 to December 2017 were enrolled in this retrospective study. The gestational age, birth weight, delivery mode, postpartum termination rate, qualified rate of follow-up assessment of pediatric heart surgery, postoperative complications, postoperative death, time of ventilator weaning, the length of postoperative hospital stay and prognosis were compared between the two groups. Results: There were no significant differences in delivery mode, premature birth rate, gestational age, birth weight, and mean maternal age between the two groups (p > 0.05). However, frequencies of terminating treatment after birth and postoperative complications were significantly higher in postnatal diagnosis group compared with prenatal diagnosis group (p< 0.05), while qualified rate of follow-up assessment of pediatric cardiac surgery was significantly lower in postnatal diagnosis group in comparison with prenatal diagnosis group (p < 0.05). Moreover, postoperative complication rate was significantly higher in the postnatal diagnosis group than prenatal diagnosis group (p < 0.05). Conclusion: Prenatal diagnosis can reduce postoperative complications after cardiac surgery and improve clinical prognosis for fetuses with complex CHD.